Emotional Instability Relates to Ventral Striatum Activity During Reward Anticipation in Females - Bayard, Frida; Abé, Christoph; Wrobel, Nathalie; Ingvar, Martin; Henje, Eva; Petrovic, Predrag (Frontiers in Behavioral Neuroscience, 2020)
Both non-emotional symptoms, such as inattention, and symptoms of emotional instability (EI) are partially co-varying and normally distributed in the general population. ADHD, which is associated with both inattention and emotional instability, has been related to lower reward anticipation activation in ventral striatum. However, it is not known whether non-emotional dysregulation, such as inattention, or EI – or both – are associated with this effect. We hypothesized that altered reward processing relates specifically to EI. To test this, twenty-nine healthy participants were recruited to this functional MRI study (n=15 females). Reward processing was studied using a modified version of the Monetary Incentive Delay task. Brown Attention-Deficit Disorder Scales questionnaire was used to assess EI and inattention symptoms on a trait level. We observed less ventral striatal activation during reward anticipation related to the EI trait in females, also when controlling for the inattention trait, but not in the whole sample or in males only. Our study suggests the existence of sex differences in the relationship between reward processing and EI/inattention traits.